Self-aligned 3D microlenses in a chip fabricated with two-photon stereolithography for highly sensitive absorbance measurement. Issue 13 (27th May 2020) - Tang, Jiukai; Qiu, Guangyu; Cao, Xiaobao; Yue, Yang; Zhang, Xiaole; Schmitt, Jean; Wang, Jing
Abstract : 3D microlenses (in plane) vi a mold replication were incorporated in the microfluidic chip for improving the performance of absorbance measurements. Abstract : Absorbance measurement is a widely used method to quantify the concentration of an analyte. The integration of absorbance analysis in microfluidic chips could significantly reduce the sample consumption and contribute to the system miniaturization. However, the sensitivity and limit of detection (LoD) of analysis in microfluidic chips with conventional configuration need improvements due to the limited optical pathway and unregulated light propagation. In this work, a 3D-microlens-incorporating microfluidic chip (3D-MIMC) with a greatly extended detection channel was innovatively fabricated using two-photon stereolithography. The fabrication was optimized with a proposed hierarchical modular printing strategy. Due to the incorporation of 3D microlenses, the light coupling efficiency and the signal-to-noise ratio (SNR) were respectively improved approximately 9 and 4 times. An equivalent optical path length (EOL) of 62.9 mm was achieved in a 3.7 μl detection channel for testing tartrazine samples. As a result, the sensitivity and LoD of the 3D-MIMC assay were correspondingly improved by one order of magnitude, compared with those of the 96-well plate assay. Notably, the 3D-MIMC has the potential to be integrated into a general microanalysis platform for multiple applications.